The difference of Mai's age and 12 is 60
so shes 72 i think
hope i'm right
Answer: 58 would be my guess, but need more info
Fraction 3 over 4x = Fraction 1 over 5. x = ___?
3Fraction 3 over 4
Fraction 11 over 20
Fraction 4 over 15
Fraction 3 over 20
Answer:
[tex]\large\boxed{x=3\dfrac{3}{4}}[/tex]
Step-by-step explanation:
[tex]\dfrac{3}{4x}=\dfrac{1}{5}\qquad\text{cross multiply}\\\\(4x)(1)=(3)(5)\\\\4x=15\qquad\text{divide both sides by 4}\\\\x=\dfrac{15}{4}\\\\x=3\dfrac{3}{4}[/tex]
Answer:
its 4/15 because u will get the answer i got 100% for that
Which of the following is not equal to the other values? cos31.7° cos211.7° cos328.3° cos(-391.7°)
Answer:
* cos 211.7 not equal the other values
Step-by-step explanation:
* Lets revise the angles in the four quadrant
- If the angle in the first quadrant is Ф, then the equivalent angles to
it in the other three quadrant are
# 180° - Ф ⇒ 2nd quadrant (sin only +ve)
# 180° + Ф ⇒ 3rd quadrant (tan only +ve)
# 360° - Ф ⇒ 4th quadrant (cos only +ve)
# -Ф ⇒ 4th quadrant (cos only +ve)
# -180 + Ф ⇒ 3rd quadrant (tan only +ve)
# -180 - Ф ⇒ 2nd quadrant (sin only +ve)
# -360 + Ф ⇒ 1st quadrant (all are +ve)
* Lets solve the problem
∵ Ф = 31.7°
∵ cos 31.7 = +ve value
∵ 180° + Ф° = 180° + 31.7° = 211.7°
∵ cos (180° + Ф°) = - cos Ф° ⇒ cos (180° + Ф°) in the 3rd quadrant is
same value as cos Ф but with -ve sign
∴ cos 211.7° = - cos 31.7°
∴ cos 31.7° ≠ cos 211.7°
∵ 360° - Ф° = 360° - 31.7° = 328.3°
∵ cos (360° - Ф°) = cos Ф° ⇒ cos (360° - Ф°) in the 4th quadrant has the
same value and sign with cos Ф°
∴ cos 328.3° = cos 31.7°
∴ cos 31.7° = cos 328.3°
∵ -391.7° + 360° = -31.7° ⇒ more then clockwise turn by 31.7°
∵ cos (-Ф°) = cos Ф° ⇒ cos (-Ф°) in the 4th quadrant has the same value
and sign with cos Ф°
∴ cos (-31.7°) = cos 31.7°
∴ cos 31.7° = cos (-390.7°)
* cos 211.7 not equal the other values
A farmer is tracking the amount of corn his land is yielding each year. He finds that the function f(x) = −x2 + 20x + 50 models the crops in pounds per acre over x years. Find and interpret the average rate of change from year 1 to year 10. The crop yield increased by 9 pounds per acre from year 1 to year 10. The crop yield decreased by 0.09 pounds per acre from year 1 to year 10. The crop yield decreased by 11 pounds per acre from year 1 to year 10. The crop yield increased by 99 pounds per acre from year 1 to year 10.
Answer: The crop yield increased by 9 pounds per acre from year 1 to year 10.
Step-by-step explanation:
To solve this we are using the average rate of change formula: Av=\frac{f(x_2)-f(x_1)}{x_2-x_1}, where:
x_2 is the second point in the function
x_1 is the first point in the function
f(x_2) is the function evaluated at the second point
f(x_1) is the function evaluated at the first point
We know that the first point is 1 year and the second point is 10 years, so x_1=1 and x_2=10. Replacing values:
Av=\frac{-(10)^2+20(10)+50-[-(1)^2+20(1)+50]}{10-1}
Av=\frac{-100+200+50-[-1+20+50]}{9}
Av=\frac{150-[69]}{9}
Av=\frac{150-69}{9}
Av=\frac{81}{9}
Av=9
Since f(x) represents the number of pounds per acre and x the number of years, we can conclude that the crop yield increased by 9 pounds per acre from year 1 to year 10.
This graph shows how the length of time a canoe is rented is related to the rental cost . What is the rate of change shown in the graph
Answer:
C. $6 per hour.
Step-by-step explanation:
Pick a convenient point on the graph. The rate of change is the
y coordinate / x coordinate.
So we pick the point near the top right corner where y = 30 and x = 5 which gives us the answer 30/5 = 6.
The rate of change shown in the graph is option B that is $3 per hour.
What is rate of change?The rate of change in a line is the difference between vertical values divided by horizontal values. It is also known as slope. It can be calculated as under:
Rate of change= y2-y1/x2-x1
How to calculate rate of change?To calculate the rate of change we need to first select two points which are in the given graph are (0,0) and (1,3)
Rate of change is equal to (3-0)/(1-0)
=3/1
means $ 3 is paid for 1 hour.
Hence the rate of change in the given graph is $3 per hour.
Learn more about rate at https://brainly.com/question/119866
#SPJ2
What is the difference of the two polynomials?
(9x2 + 8x) – (2x2 + 3x)
(9x^2 + 8x) – (2x^2 + 3x)
Subtract like terms:
9x^2 - 2x^2 = 7x^2
8x - 3x = 5x
The difference is 7x^2 + 5x
Jovian decided to collect data to determine if students' heights and their shoe sizes are correlated. He determined the data to have a correlation coefficient of 0.98. What does this r value indicate? No correlation A strong, positive correlation A weak, positive correlation A negative correlation
Answer:
A strong positive correlation
Step-by-step explanation:
A strong correlation when the correlation coefficient is close to 1 or -1. If the correlation coefficient is close to positive 1, then it is a positive strong correlation coefficient. If the correlation coefficient is close to negative 1, then it is a negative strong correlation coefficient.
Answer:
The r-value indicate A strong positive correlation
Step-by -step-explanation:
The following information should be considered:
A strong correlation arise when the correlation coefficient is nearest to 1 or -1. In the case when the correlation coefficient is nearest to positive 1, so it is a positive strong correlation coefficient. In the case when the correlation coefficient is nearest to negative 1, so it is a negative strong correlation coefficient.Learn more: https://brainly.com/question/18269454?referrer=searchResults
Choose the function that the graph represents.
Click on the correct answer.
y = f(x) = log1x
y = f(x) = x4
y = f(x) = log(1/4)*
Final answer:
To identify which function the graph represents, analyze the shape and pattern of the graph. The correct function could either be a polynomial such as y = x^4, which has a sharply rising curve, or a logarithmic function with a declining curve due to having a base between 0 and 1, like y = log(1/4)x, but not y = log1x as this is not mathematically valid.
Explanation:
The question requires the identification of a function based on its graph. Since the properties of functions are known, such as the logarithmic function increasing as x increases, and the behavior of exponential functions and their inverses, we can analyze the options given. The function y = log1x is not valid as the base of a logarithm cannot be 1. The function y = x4 is a polynomial function with a graph that rises sharply for positive and negative values of x. Lastly, y = log(1/4)x represents a logarithmic function with base 1/4, which is a declining curve because the base is between 0 and 1.
To choose the correct function that a graph represents, one should look for key characteristics such as the shape of the graph, increase or decrease pattern, as well as specific points like asymptotes or intercepts. If the graph is increasing as x increases and resembles a typical logarithmic curve, the correct choice is a logarithmic function. If the given graph is a sharp rising curve for all x-values and looks like a polynomial, then y = x4 would be correct. The given functions need to be analyzed based on their mathematical properties to select the one that best describes the graph in question.
If the 7th of an AP is equal to 11 times the 11th term, find the 18th term
Answer:
-33 or 33
Step-by-step explanation:
The seventh term of an AP is written as:
[tex]a + 6d[/tex]
The eleventh term of an AP is written as:
[tex]a + 10d[/tex]
If the 7th term is 11 times the 11th term, then;
[tex]a + 6d = 11(a + 10d)[/tex]
Expand to get:
[tex]a + 6d = 11a + 110d[/tex]
[tex]11a - a = 6d - 110d[/tex]
[tex]10a = - 104d[/tex]
[tex] \frac{a}{d} = - \frac{104}{10} [/tex]
[tex] \frac{a}{d} = - \frac{52}{5} [/tex]
We must have a=-52 and d=5
Or
a=52 and d=-5
For the first case, the 18th term is :
[tex] - 52 + 5 \times 17 = 33[/tex]
For the second case,
[tex]52 - 5 \times17 = - 33[/tex]
Which represents the solution of the system of equations, y=x^2-x+1 and y=x? Determine the solution set by graphing
Answer:
(1,1)
Step-by-step explanation:
We have the following system:
[tex]y=x^2-x+1[/tex]
[tex]y=x[/tex]
We are going to plug the 2nd equation into the 1st eqaution giving us:
[tex]x=x^2-x+1[/tex]
Now time to solve [tex]x=x^2-x+1[/tex].
[tex]x=x^2-x+1[/tex]
Subtract x on both sides:
[tex]0=x^2-2x+1[/tex]
Now this actually not too bad. This a perfect square trinomial. That is it is of the form [tex]a^2x^2+2abx+b^2[/tex] which equals [tex](ax+b)^2[/tex].
So solving [tex]0=x^2-2x+1[/tex] is equivalent to solving [tex]0=(x-1)^2[/tex]
In order to solve [tex]0=(x-1)^2[/tex], we just need to know when x-1=0 which is at x=1. I got by adding 1 on both sides of x-1=0
Now remember y=x means we have the solution (1,1).
Okay, I'm going to leave all of this algebra here. I'm going to graph this without a graphing calculator.
[tex]y=x[/tex] is a line with slope 1 and y-intercept 0.
[tex]y=x^2-x+1[/tex] is a parabola. The vertex isn't obvious to me right now without the algebra but I do know the parabola is open up because the coefficient of x^2 being positive.
So let's find the vertex.
I'm going to start with the x-coordinate which is -b/(2a).
Compare [tex]x^2-x+1[/tex] to [tex]ax^2+bx+c[/tex] and you should see that [tex]a=1,b=-1,c=1[/tex].
So [tex]-\frac{b}{2a}=-\frac{-1}{2(1)}=\frac{1}{2}[/tex]
So the vertex occurs when the x-coordinate is 1/2.
To find the correspond y-value just use the equation that relations x and y.
That is use [tex]x^2-x+1[/tex].
Replace x with 1/2.
[tex](\frac{1}{2})^2-(\frac{1}{2})+1[/tex]
[tex]\frac{1}{4}-\frac{1}{2}+1[/tex]
Find a common denominator.
[tex]\frac{1}{4}-\frac{2}{4}+\frac{4}{4}[/tex]
[tex]\frac{1-2+4}{4}[/tex]
[tex]\frac{3}{4}[/tex]
So the vertex is at (1/2,3/4) and the parabola is open up.
When you plug in 0 into [tex]x^2-x+1[/tex] you get [tex]0^2-0+1=1[/tex] so the ordered pair (0,1) is on the parabola.
Using symmetry about the line x=1/2 we know that (1,1) is also on this graph.
Let's use this information to produce a graph now.
Now our answer appears to be (1,1) in the graph.
We can check this answer by plugging in (1,1) into our system and see if both equations check out:
[tex]y=x[/tex] gives us 1=1 which is true. So we are good there.
[tex]y=x^2-x+1[/tex] gives us [tex]1=1^2-1+1[/tex] which is true. So we are good there.
The work for showing [tex]1=1^2-1+1[/tex].
[tex]1^2-1+1[/tex]
[tex]1-1+1[/tex]
[tex]0+1[/tex]
1
So the point (1,1) checks out for both of our equations which means it is a common point amongst the equations given.
Which of the following circles lie completely within the fourth quadrant?
Check all that apply.
Answer:
C and D
Step-by-step explanation:
The fourth quadrant is where all the points are in the form (positive, negative).
The center and radius of [tex](x-h)^2+(y-k)^2=r^2[/tex] is (h,k) and r, respectively.
Let's look at the centers and the radius of each of these choices:
A) This one has center (4,-2) and radius [tex]\sqrt{32} \approx 5.7[/tex].
If you add 5.7 to -2 you get a positive number and we needed it negative.
Not this choice; moving on.
B) This one has center (-3,2) and radius [tex]\sqrt{25}=5[/tex].
The center is not even in quadrant 4; moving on.
C) This one has a center (3,-4) and radius 1.
Add 1 to 3 you get 4.
Subtract 1 from 3 you get 2.
Those x's are positive so that looks good so far.
Add 1 to -4 you get -3.
Subtract 1 from -4 you get -5.
Those y's are negative so that looks good.
This circle is in quadrant 4 and doesn't go outside it.
D) This one has center (5,-7) and radius 4.
Add 4 to 5 you get 9.
Subtract 4 from 5 you get 1.
Positive x's is good.
Add 4 to -7 you get -3.
Subtract 4 from -7 you get -11.
Those are negative so that looks good.
[tex](x-3)^{2} +(y+4)^{2} =1[/tex], [tex](x-5)^{2} +(y+7)^{2} =16[/tex] lie completely within the fourth quadrant.
What is fourth quadrant?Quadrant IV: The fourth quadrant is in the bottom right corner of the plane. In this coordinate X has positive values and y has negative values.
According to the question
We have to find the circles lie completely within the fourth quadrant.
Observing the below graph, These two circle lie completely within the fourth quadrant.
[tex](x-3)^{2} +(y+4)^{2} =1[/tex]
[tex](x-5)^{2} +(y+7)^{2} =16[/tex]
These circles lie bottom right corner of the plane.
From the given graphs below Option C and D lie completely within the fourth quadrant.
[tex](x-3)^{2} +(y+4)^{2} =1[/tex], [tex](x-5)^{2} +(y+7)^{2} =16[/tex] lie completely within the fourth quadrant.
Find out more information about fourth quadrant here
brainly.com/question/2364327
#SPJ2
Rewrite each sum as a product of The GCF of the addends and another number 9 + 27
Answer:
9*4
Step-by-step explanation:
We can Factor out a 9 from each term
9 + 27
9 (1+3)
9 (4)
9*4
Find the diagonal of a square whose sides are of the given measure. Given = 3sqrt2
ANSWER
The diagonal of the square is 6 units.
EXPLANATION
A diagonal of a square divides the square into two congruent right isosceles triangles.
Let the sides of the square be 's' units. Then, the Pythagoras Theorem says that, the sum of the squares of the shorter legs will be equal to the square of the hypotenuse.
Let the diagonal which is the hypotenuse be 'd' units.
Then,
[tex] {d}^{2} = {s}^{2} + {s}^{2} [/tex]
[tex] \implies \: {d}^{2} = 2{s}^{2}[/tex]
From the question, the side length of the square is
[tex]s = 3 \sqrt{2} \: units[/tex]
We plug in this value to obtain:
[tex]\implies \: {d}^{2} = 2{(3 \sqrt{2} )}^{2}[/tex]
Or
[tex]\implies \: {d}^{2} = 2 \times { {3}^{2} (\sqrt{2} )}^{2}[/tex]
[tex]\implies \: {d}^{2} = 9 \times 2 \times 2 = 36[/tex]
We take the positive square root of both sides to get:
[tex]d = \sqrt{36} [/tex]
[tex]d = 6 \: units[/tex]
Given that f(x) = x2 + 6x – 2, g(x) = x – 7, and h(x) = x + 4 find each function.
(f + g)(x)
options are
A) x2 + 7x – 9
B) x2 + 7x + 2
C) x2 + 5x – 6
D) x2 + 5x + 5
Answer:
A) x² + 7x - 9
Step-by-step explanation:
Deduct\Add each like-term to arrive at your answer.
if A= [-5,7] and B= [6,10], then find A u B
Answer:
[tex]\large\boxed{A\ \cup\ B=[-5,\ 10]}[/tex]
Step-by-step explanation:
Look at the picture.
The union of two sets A and B (A ∪ B) is the set of elements which are in A, in B, or in both A and B
What is the multiplicative inverse of −3/5?
Answer:
The multiplicative inverse is -5/3
Step-by-step explanation:
Multiplicative inverse means we want to end up with 1
-3/5 * what =1
Multiply by 5 to clear the fraction
-3/5 * what *5 = 1*5
-3 * what = 5
Divide by -3 to isolate what
-3*what /-3 = 5/-3
what = -5/3
The multiplicative inverse is -5/3
last week 24,000 fans attended a football match. this week three times as many bought tickets, but one-sixth of them cancelled their tickets. how many are attending this week.
A.48,000
B.54,000
C.60,000
D.72,000
Please explain, Thank you!
Answer:
C. 60,000
Step-by-step explanation:
Given
24,000 fans attended a football matchthree times as many bought ticketsone-sixth of them cancelled their ticketsThree times as many bought tickets
24,000 * 3 = 72,000
one-sixth of them cancelled their tickets
72,000 * 1/6 = 12,000
Subtract
72,000 - 12,000 = 60,000
Answer
60,000 people are attending this week
This week, 60,000 fans are attending the football match.
Explanation:To find the number of fans attending the football match this week, we need to start with the number of fans who bought tickets. This week, three times as many fans bought tickets as last week, so there were 3 * 24,000 = 72,000 fans who bought tickets. However, one-sixth of them cancelled their tickets, which means 1/6 * 72,000 = 12,000 fans cancelled. Therefore, the number of fans attending the match this week is 72,000 - 12,000 = 60,000.
Learn more about Attendance at Football Match here:https://brainly.com/question/32850715
#SPJ2
Evaluate the expression when y=6. Y^2-5y-8
Answer:
-2
Step-by-step explanation:
6^2 = 36
5 x 6 = 30
36 - 30 - 8 = -2
whats the solution of -8/2y-8= 5 divided y+4 minus 7y+8 divided y^2-18
Answer:
We can find the answer to your question by using a computational tool or any similar software
The equation is
-8/2*y - 8 = 5/y + 4 -7y + 8/y^2 - 18
-4*y + (- 8-4 + 18) = 5/y -7y + 8/y^2
-4*y + 6 = 5/y -7y + 8/y^2
-4*y + 7y + 6 = 5/y + 8/y^2
3y + 6 = 5/y + 8/y^2
We multiply by y^2
3y^3 + 6y^2 = 5y + 8
3y^3 + 6y^2 -5y - 8 = 0
See image below for result of the equation
What is the measure of
Answer:
D. 74°
Step-by-step explanation:
∠XYZ is an inscribed angle, where its vertex is located on the circle and two intersecting chords form the vertex.
An inscribed angle is equal to HALF of the intercepted arc, which is the arc that is between the two points where the chords hit.
In this picture, the intercepted arc is the red part of the outside of the circle.
Since you are given the measurement of the intercepted arc, you can find the measure of the inscribed angle by finding half of 148°.
Therefore, the inscribed angle is 148° divided by 2, giving us 74°.
The measure of the inscribed angle, ∠XYZ, is D. 74°.
Ellie wants to double her savings of £8000 by investing her money for 16 years.
What interest rate does
she need to look for?
Answer:
She need a interest rate of 6.25%
Step-by-step explanation:
we know that
The simple interest formula is equal to
[tex]A=P(1+rt)[/tex]
where
A is the Final Investment Value
P is the Principal amount of money to be invested
r is the rate of interest
t is Number of Time Periods
in this problem we have
[tex]t=16\ years\\ P=\£8,000\\ A=\£8,000*2=\£16,000\\r=?[/tex]
substitute in the formula above and solve for r
[tex]16,000=8,000(1+16r)[/tex]
[tex]16r=2-1[/tex]
[tex]r=1/16[/tex]
[tex]r=0.0625[/tex]
Convert to percentage
[tex]r=0.0625*100=6.25\%[/tex]
Find the values of x and y
1-2i/ 2+i + 4-i/3+2i = x+iy
Answer:
[tex]x=\frac{10}{13}[/tex] and [tex]y=-\frac{24}{13}[/tex]
Step-by-step explanation:
The given complex number equation is:
[tex]\frac{1-2i}{2+i}+\frac{4-i}{3+2i}=x+yi[/tex]
We simplify the LHS and compare with the RHS
We collect LCD on the left to get:
[tex]\frac{(1-2i)(3+2i)+(4-i)(2+i)}{(2+i)(3+2i)}=x+yi[/tex]
[tex]\frac{3+2i-6i+4+8+4i-2i+1}{6+4i+3i-2}=x+yi[/tex]
Simplify to get:
[tex]\frac{16-2i}{4+7i}=x+yi[/tex]
Rationalize the LHS:
[tex]\frac{(16-2i)(4-7i)}{(4+7i)(4-7i)}=x+yi[/tex]
Expand the numerator using the distributive property and the denominator using difference of two squares.
[tex]\frac{64-112i-8i-14}{16+49}=x+yi[/tex]
Simplify to get:
[tex]\frac{50-120i}{65}=x+yi[/tex]
[tex]\frac{10-24i}{13}=x+yi[/tex]
[tex]\frac{10}{13}-\frac{24}{13}i=x+yi[/tex]
By comparing real parts and imaginary parts; we have;
[tex]x=\frac{10}{13}[/tex] and [tex]y=-\frac{24}{13}[/tex]
What's the proper name of this quadrilateral?
A. Trapezoid
B. Square
C.Rhombus
D. Parallelogram
Answer:
Trapezoid- A.
Answer:
A. Trapezoid
Step-by-step explanation:
The proper name of this quadrilateral is a trapezoid.
The picture might look confusing because the trapezoid is upside down.
However, it still counts as a trapezoid.
Question 2(Multiple Choice Worth 5 points) (08.02 MC)What is the mean absolute deviation for 2, 9, 1, 7, 8, and 9? 1 3 6 8
Answer:
Mean Absolute Deviation = 3.
Step-by-step explanation:
The mean = (2 + 9 + 1 + 7 + 8 + 9) / 6
= 36/6
= 6.
Subtract 6 from each number:
2 - 6 = -4 Absolute value = 4
9 - 6 = 3
1 - 6 = -5 Absolute value = 5
7 - 6 = 1
8 - 6 = 2
9 - 6 = 3
Total = 4 + 3 + 5 + 1 + 2 + 3 = 18
Mean Absolute Deviation = 18 / 6 = 3.
Answer:
B: 3
Step-by-step explanation:
First you will take the numbers and add them. The equation would be 2 + 9 + 1 + 7 + 8 + 9. That equals 36.
Then, you may divide that by 6 (how many numbers there were) and that is your mean (also 6).
Next, you find the how far each number is from the mean using absolutes. Those values are 4, 3, 5, 1, 2, and 3.
Finally, add those together to get 18, then divide by how many numbers there were (6) that to get the mean absolute deviation (3).
Hope this helped! :)
Suppose you invest $300 at annual interest rate of 4.5% compounded continuously.
How much will you have in the account after 7.5 years?
Answer:
[tex]\$420.43[/tex]
Step-by-step explanation:
we know that
The formula to calculate continuously compounded interest is equal to
[tex]A=P(e)^{rt}[/tex]
where
A is the Final Investment Value
P is the Principal amount of money to be invested
r is the rate of interest in decimal
t is Number of Time Periods
e is the mathematical constant number
we have
[tex]t=7.5\ years\\ P=\$300\\ r=0.045[/tex]
substitute in the formula above
[tex]A=300(e)^{0.045*7.5}[/tex]
[tex]A=\$420.43[/tex]
PLEASE HELP!!
Match each polynomial with the appropriate explanation regarding the roots of the related polynomial equation.
Answer:
Part 1) [tex](x+4)(x-1)(x-2)(x-4)[/tex]
The related polynomial equation has a total of four roots, all four roots are real
Part 2) [tex](x+1)(x-1)(x+2)^{2}[/tex]
The related polynomial equation has a total of four roots, all four roots are real and one root has a multiplicity of 2
Part 3) [tex](x+3)(x-4)(x-(2-i))(x+(2-i))[/tex]
The related polynomial equation has a total of four roots, two roots are complex and two roots are real
Part 4) [tex](x+i)(x-i)(x+2)^{2}[/tex]
The related polynomial equation has a total of four roots, two roots are complex and one root is real with a a multiplicity of 2
Step-by-step explanation:
we know that
The Fundamental Theorem of Algebra states that: Any polynomial of degree n has n roots
so
Part 1) we have
[tex](x+4)(x-1)(x-2)(x-4)[/tex]
The roots of this polynomial are
x=-4, x=1,x=2,x=4
therefore
The related polynomial equation has a total of four roots, all four roots are real
Part 2) we have
[tex](x+1)(x-1)(x+2)^{2}[/tex]
The roots of this polynomial are
x=-1, x=1,x=-2,x=-2
therefore
The related polynomial equation has a total of four roots, all four roots are real and one root has a multiplicity of 2
Part 3) we have
[tex](x+3)(x-4)(x-(2-i))(x+(2-i))[/tex]
The roots of this polynomial are
x=-3, x=4,x=(2-i),x=-(2-i)
therefore
The related polynomial equation has a total of four roots, two roots are complex and two roots are real
Part 4) we have
[tex](x+i)(x-i)(x+2)^{2}[/tex]
The roots of this polynomial are
x=-i, x=i,x=-2,x=-2
therefore
The related polynomial equation has a total of four roots, two roots are complex and one root is real with a a multiplicity of 2
Please help I need answers
Answer:
[tex]-\frac{25}{3}[/tex]
Step-by-step explanation:
To isolate for x, start by multiplying both sides by 2.5.
[tex]\frac{25}{3} =-x[/tex]
Next, divide both sides by -1.
[tex]\frac{-25}{3} =x[/tex]
Answer:
x = -25/3
Step-by-step explanation:
10/3 = x / (-5/2)
Multiply each side by (-5/2) to isolate x
-(5/2) * 10/3 = -5/2 * (x / (-5/2))
-50/6 = x
Divide the top and bottom by 2 on the left hand side
-25/3 =x
Changing to a mixed number ( if required)
3 goes into 25 8 times ( 3*8=24) with 1 left over(25-24=1)
x = -8 1/3
Slope of the line through the points (2,1) and (4,2) is
Answer:
slope = [tex]\frac{1}{2}[/tex]
Step-by-step explanation:
Calculate the slope m using the slope formula
m = (y₂ - y₁ ) / (x₂ - x₁ )
with (x₁, y₁ ) = (2, 1) and (x₂, y₂ ) = (4, 2)
m = [tex]\frac{2-1}{4-2}[/tex] = [tex]\frac{1}{2}[/tex]
[tex]\huge\boxed{\frac{1}{2}}[/tex]
We can use [tex]\frac{y_2-y_1}{x_2-x_1}[/tex] to find the slope, where [tex](x_1, y_1)[/tex] and [tex](x_2, y_2)[/tex] are both points.
Plug in the values. [tex]\frac{2-1}{4-2}[/tex]
Subtract. [tex]\frac{1}{2}[/tex]
(2x-6) times (3x^2-4x-5)
For this case we must multiply the following expression:
[tex](2x-6) (3x ^ 2-4x-5)[/tex]
Applying distributive property we have:
[tex](2x) (3x ^ 2) - (2x) (4x) - (2x) (5) - (6) (3x ^ 2) + (6) (4x) + (6) (5) =[/tex]
By definition of multiplication of powers of the same base, we have to put the same base and add the exponents:
[tex]6x ^ 3-8x ^ 2-10x-18x ^ 2 + 24x + 30 =[/tex]
Adding similar terms:
[tex]6x ^ 3-26x ^ 2 + 14x + 30[/tex]
Answer:
[tex]6x ^ 3-26x ^ 2 + 14x + 30[/tex]
9y – 2 + y= 5y + 10
Answer:
y=2.4
Step-by-step explanation:
9y-2+y=5y+10
(combine like terms)
10y-2=5y+10
(subtract 5y from both sides)
5y-2=10
(add 2 to both sides)
5y=12
(divide both sides by 5)
y=2.4